Business Strategic Management Processes and Practices: An Analytical Study with Reference to India: Examining the Corporate Strategy Practices of Indian Small Business Enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Strategy is thought to be a nitty gritty arrangement for a business in making progress. Administrators utilize strategy to accomplish result. Key management practices and organization execution in private venture undertakings SBEs goes together, however most Small business endeavors put less accentuation on making powerful technique for enhanced execution. Corporate methodology questions identifying with the proper measures of execution, the rate of development and degree of expansion, and the approaches to activate assets and create essential abilities are of present and high significance to Indian organizations. In the coming decade, they have to receive thorough and suitable corporate strategy approaches as they confront an unpredictable, quick changing, and globalizing business condition. In view of an evaluation of the strategies, corporate methodology is considered as a reaction to objectives in the transformative and rising settings and the point of view of the coming decade is taken to investigate the Indian business circumstance. In the accompanying paper vital management of different Indian organizations has been clarified.